ASEAN as an international organization international law and region-building in Southeast Asia - Bagulaya, José Duke (Manila, Philippines University of Santo Tomas Publishing House, 2022)
The book critically examines ASEAN's transformation into an international legal entity, exploring the concept of "people" and offering a people's reading of the ASEAN Charter. It critiques ASEAN's constitutional, extra-constitutional, and practical limitations, while questioning the notion of community within ASEAN's discourses. Combining international law, politics, and culture, it offers insightful perspectives for legal scholars and students.
Chapter I: The Legal Turn in ASEAN Studies: Themes and Problems of a New Scholarship and the Possibility of an Interdisciplinary Approach to ASEAN -- Chapter 2: The Authors Do Not Speak: A People's Reading of the ASEAN Charter -- Chapter 3: ASEAN as Wayang Kulit: A Critique of the Constitutional, Extra-constitutional, and Practical Fetters of ASEAN -- Chapter 4: International Organization and Community: Interrogating ASEAN's Fictions of Community.
Includes bibliographical references.
Keywords: ASEAN; Regionalism (International organization); Regionalism -- Southeast Asia; International law -- Southeast Asia